2019
DOI: 10.1515/mosr-2019-0012
|View full text |Cite
|
Sign up to set email alerts
|

Personal Entrepreneurial Competencies of Participants in Experiential Entrepreneurship Education

Abstract: This study aims to analyse the personal entrepreneurship competencies of students participating in experiential entrepreneurship program. In the theory part, the paper analyses the recent studies done in the entrepreneurship competencies field and discusses the experiential entrepreneurship concept. Research focuses on finding out the level of personal entrepreneurial competencies of participants of experiential entrepreneurship education, also analysing the demographic profile of the respondents, comparing it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…In addition, a positive attitude, competitiveness, determination, questioning everything, creativity as well as controlling emotions, coping with stress, the ability to make decisions or the willingness to take challenges allow you to look at the market from a different perspective, which inspires and encourages young people to connect the future with running their own companies. The conclusions drawn are also confirmed by the research conducted among Lithuanian students, which found that students intending to run their own business are characterized by: persistence, goal setting, information-seeking and self-confidence (Kyguolienė and Švipas, 2019). As in foreign studies (Solezvick, 2019), a very important aspect for students of the University of Economics in Cracow is the clear relationship between building entrepreneurial competences and education in the field of entrepreneurship.…”
Section: Discussion Of Resultssupporting
confidence: 62%
See 4 more Smart Citations
“…In addition, a positive attitude, competitiveness, determination, questioning everything, creativity as well as controlling emotions, coping with stress, the ability to make decisions or the willingness to take challenges allow you to look at the market from a different perspective, which inspires and encourages young people to connect the future with running their own companies. The conclusions drawn are also confirmed by the research conducted among Lithuanian students, which found that students intending to run their own business are characterized by: persistence, goal setting, information-seeking and self-confidence (Kyguolienė and Švipas, 2019). As in foreign studies (Solezvick, 2019), a very important aspect for students of the University of Economics in Cracow is the clear relationship between building entrepreneurial competences and education in the field of entrepreneurship.…”
Section: Discussion Of Resultssupporting
confidence: 62%
“…Since the 1990s, the research, in that approach, are still being continued (i.a. Chandler and Jansen, 1992;Johannisson, 1993;Bird, 1995;Man et al, 2002;Mitchelmore and Rowley, 2010;Kyndt and Baert, 2015;Zadeh et al 2017;Solesvick 2019;Kyguolienė and Švipas 2019;Wang et al 2019). On Polish ground, one can notice a relatively modest amount of research concerning the conceptualisation of the notion of entrepreneurial competences.…”
Section: Outline Of Defi Ning and Examining Entrepreneurial Competencesmentioning
confidence: 99%
See 3 more Smart Citations